Disorders of Puberty in Severely Neurologically Impaired Children: Is Delayed Puberty an Underestimated Problem? - Calcaterra, Valeria; Cena, Hellas; De Silvestri, Annalisa; Di Mitri, Marco; Pelizzo, Gloria (Frontiers in Pediatrics, 2019)
Introduction: In children with disabilities, precocious puberty (PP) has been reported, however there is a paucity of studies on delayed puberty (DP) in neurologically impaired (NI) children. Patients and Methods: We retrospectively evaluated 65 patients with severe disabilities (6–18 years). DP was considered whenever the following criteria where satisfied, respectively, for girls and boys, absence of breast development by age 13 or menarche by age 15, absence of at least 4 mL testicular growth volume or 2.5 cm length by age 14. PP was defined as the presence of puberty signs at <8 and 9 years of age, respectively, for girls and boys. In all patients, a physical examination was performed and a family history of DP was obtained. A hormonal panel was evaluated when puberty disorders were detected. As a control group we evaluated 50 age-matched healthy subjects. Results: Puberty disorders were observed in 12 NI patients and in one control (18.5 vs. 2%, p < 0.01). DP was detected in 8 NI subjects (3M/5F) and in one healthy boy (p = 0.04), without differences between genders among patients from the NI group (p = 0.2), and compared with the controls (p = 0.4). In five of the eight NI subjects, Tanner stage 1 was observed; in three subjects adrenarche was present without pubertal progression for more than 2 years. Low levels of gonadotropins were detected in all NI subjects with DP. The number of subjects with a BMI <-3SDS was higher in NI patients with DP compared to NI subjects with normal puberty (p < 0.01); normal weight was detected in one healthy boy. The family history for pubertal delay was negative in all NI patients with DP and positive in the control subject. Conclusion: NI children and adolescents may experience delayed pubertal changes. An endocrinological follow-up with pubertal development monitoring is strongly recommended in order to evaluate whether targeted interventions may improve outcomes.